The effect of Cu additions in FePt–BN–SiO2 heat-assisted magnetic recording media. (23rd December 2020) - Streubel, Robert; N'Diaye, Alpha T; Srinivasan, Kumar; Kalitsov, Alan; Jain, Shikha; Ajan, Antony; Fischer, Peter
Abstract: Structural and chemical order impact magnetic properties of solids, which are governed by spin–orbit coupling and exchange interaction. The ordered L 10 phase of FePt is a key material to heat-assisted magnetic recording; to enable high storage density, a solid understanding is needed of structural and chemical disorder at small length scales, as well as associated modifications of the electronic band structure. Here, we investigate the effect of boron and copper additions (≲6 mol% Cu) on structural and magnetic properties of L 10 FePt granular media. Two copper-driven mechanisms, although competing, can lead to improvements in both structural and magnetic properties. In particular, the Cu substitution on the Fe-site leads to a degradation of magnetic properties due to the delocalized electron orbitals originating from a larger Cu d -orbital occupancy. At the same time, Cu substitution leads to an enhanced crystallographic order and consequently magneto-crystalline anisotropy, which offsets the former effect to a large extent. Our study is based on magnetometry, x-ray absorption spectroscopy, ab-initio calculations and a phenomenological theory of disordered FePt granular media. We do not observe a sizable modification to Fe moments and electronic configuration; Cu reveals two different resonances associated with the presence and absence of Cu–B bonds that vary with total Cu concentration.